Common Grammatical Errors in Oral Communication Made by Indonesian EFL Learners - Nurillah Najla; Sitti Fatimah (Journal of English Language Teaching, 2020)
As EFL learners who learn English as their major at school, they still face difficulties to speak with appropriate and correct grammar. It causes some mistakes and errors with grammar when they speak. The purposes of this research are to identify and classify the type of errors in students’ speaking performance based on linguistic category in morphological and syntactical level, and to find out the causes of EFL learners make grammatical errors based on intralingual aspect. The research design was qualitative descriptive research. The sources of this research data is from students' voice recordings when the researcher interviewed them by phone one by one. The participant of this research was thirty second year students majoring English in Universitas Negeri Padang which enrolled in 2019. The interview was used to collect the data, and the data were analyzed by using Linguistic Category Classification from Politzer and Ramirez. Based on the result of data analysis, 16 kinds of grammatical errors were found. The dominant kind of grammatical error which if found in EFL learners’ speaking was simple past tense. Then, for the causes of EFL learners’ error in intralingual transfer aspect based on James theory was incomplete rule application, overlooking co-occurrences restriction, overgeneralization, and exploiting redundancy.